A Mixed-Methods Investigation of the Experiences of Migrant Care Workers Caring for People with Dementia in Australian Residential Aged Care Facilities - Adebayo, Omobola Abake (Curtin University, 2022)
An explanatory sequential mixed-methods research design was used to investigate the level of knowledge of dementia among residential aged care facilities (RACFs) migrant care workers and the impact of the resettlement challenges on their well-being and retention in RACFs. A total of 272 migrant care workers participated in a national cross-sectional survey (Phase One) and 20 participated in semi-structured qualitative interviews (Phase Two). Participants had a moderate level of knowledge of dementia and knowledge deficiencies in the cause and physical symptoms associated with the comorbidities of dementia. Migrant care workers can experience acculturation stress without having a measurable impact on their mental health.